About observation of the meson exchange current in inelastec electron scatteringon ⁴He nucleus - Buki, A.Yu. (Вопросы атомной науки и техники, 2002)
The problem of the experimental detection of meson exchange current contribution in inelastic electron scattering on ⁴He nucleus is examined. The upper limit of this contribution is finded for q = 0.75 - 1.50 fm⁻¹.